Az egyetemi szintű közgazdászképzés első lépései Győrben - Veress, József (Tér - Gazdaság - Ember/Journal of Region, Economy and Society, 2023)
University-level economics education on the banks of the Rába River now has a quarter-century history. For younger readers, I would like to point out that the real challenge was never economics education, but becoming a university. According to the rules at the time, the presence of accredited university courses within the institution was an essential prerequisite for the award of a university title. The leaders of the College and the Universitas Foundation saw the Faculty of Economics as playing the role of the Trojan horse. At that time, law education was provided in an outsourced form (ELTE), which was much more convenient and at the same time less risky. As we know, this large-scale project had a happy ending, with the university being founded in 2002. The relevant faculty was named Law and Economics, not the other way around. This did not frustrate me as an economist and founding dean, but it was somewhat unfair to my colleagues at the Faculty of Economics, who worked at a tremendous pace. However, the unspoken principle in Győr, “the university above all else,” naturally overrides all of this.